粘塑性流体弹流润滑的研究进展 - 刘剑平 (Jixie chuandong)
The background and status of the forming of Elastohydrodynamic Lubrication in domestic and overseas are introduced in this paper.Some problems about Elastohydrodynamic Lubrication that need to solve are specified.